CAN YOU HEAR MY VOICE?: ANALYSIS OF STUDENTS EXPERIENCE FROM A SEMESTER OF SUDDEN ONLINE LEARNING - Fadzlin Ahmadon; Hajar Izzati Mohd Ghazalli; Hazlifah Mohd Rusli (Journal of Islamic, Social, Economics and Development, 2022)
Much like their peers in many universities around the world, students of Universiti Teknologi MARA (UiTM) experienced their first full-time implementation of online learning during the 2020 government-mandated lockdown. An attempt was made to understand the preparedness and concerns of students prior to the carrying out of online learning in UiTM. Analysis of the questionnaire disclosed students’ concerns on their ability to understand and focus with classes and a fear of technical failures. After the semester ended, another questionnaire was issued to the same set of students with more questions exploring their opinions, preferences and experience. Review of answers discovered aspects of online learning liked and disliked by students, and also factors that most negatively impacted their online learning experience. Additionally, a further investigation on responses of students that answered both questionnaires showed some of them changed their minds on several aspects after experiencing online learning. This discloses a possibility of further acceptance of the online learning system when students’ fears and issues are properly addressed in the future.